How do firms in Argentina get financing to export? - Castagnino, Tomás (2012)
This paper delves into the importance of access to financing for the performance of firms in export markets. Based on a unique microeconomic database that combines data on Argentine firms’ characteristics and export performance with information on their domestic and external financing, we provide a rich insight into their financing patterns. Through the use of a descriptive and econometric analysis, we have found that: i) access to bank credit increases the probability of firms’ entry into export markets, ii) once firms become exporters, bank financing becomes less important and it is the access to foreign financing what helps to explain their success in foreign markets. Also, to study the duration of firms in export markets, we estimate survival functions by firm size, using the Kalpan-Meier estimator. We find that the probability of survival increases with firm’s size in the earlier years of exporting. Once firms become regular exporters, their permanence in export markets becomes less dependent on their size.